TEMPO-oxidized cellulose fiber from spent coffee ground: Studying their properties as a function of particle size - Hooriyeh Rahmani Khoshk; Marzieh Moeenfard (Heliyon)
The applicability of cellulose and its derivatives is greatly depends on their attributes such as aspect ratio, morphology, surface chemistry, crystallinity, as well as their thermal and mechanical properties. However, these attributes can alter according to the utilized raw material, size classifications, extraction techniques, or fibrillation methods. Among these, the effect of raw material particle size on cellulose properties has received limited attention in scientific studies. Therefore, this study aimed to investigate the effect of different particle sizes of spent coffee grounds (SCG) (A: 850–1400 μm, B: 500–850 μm, C: 355–500 μm) on the physicochemical properties of TEMPO-oxidized cellulose (TOC). The freez-dried TOC was characterized in terms of functional groups, morphology, width diameter, crystallinity, carboxyl content, charge density, thermal properties, and re-dispersibility in water. Successful oxidation in all samples was confirmed by the presence of a sodium carboxylate peak in the FTIR spectrum. Higher thermal resistance, carboxyl content, as well as improved physical stability of the re-dispersed suspension were observed in A-TOC sample. Unlike B and C-TOC, A-TOC was favored sample for obtaining fibrillated cellulose with crystallinity of 49.92 %. In contrast, production process significantly damaged the crystalline regions in finer particles and reduced the crystallinity of B and C-TOC to values ranging from 35 to 37 %. In conclusion, finer SCG particles were highly sensitive to reaction conditions and showed high tendency toward dissolution, which make them unsuitable candidates for fiber fabrication. In terms of SCG, only coarse particles (A: 850–1400 μm) were found to be ideal for producing oxidized cellulose fibers.